Método montessori y su incidencia en el desarrollo de la identidad y autonomía de los niños del sub nivel inicial 1 de la Unidad Educativa Francisco Huerta Rendón, cantón Babahoyo, Provincia Los Ríos - Baque Narvaez, Dayanna Yonela (2022)
This research project is detailed with a descriptive survey whose objective is to make known the Montessori Method benefits the identity and autonomy of the infant, in order to apply and improve the learning capacity of children of the initial sub level 1 of the Unit. Educational Francisco Huerta Rendón”, Babahoyo City. This method promotes independence, freedom and encourages self-regulation by guiding children to build their own path, inspiring the child to form their character and express their personality, provides security and respect, facilitates the development of the child's sense of responsibility and self-discipline. The Montessori methodology develops and contributes a lot within its four most important areas, such as its language, cognitive, social-affective and motor skills, which highlights a clear vision in children because they can perform various actions by themselves and can ask for help from others. An adult as long as it may be necessary. To which this method has a perspective as an environment designed to meet the needs of your self-discovery.